2007
DOI: 10.1007/s00284-007-9050-3
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Pyrimidine Salvage in Pseudomonas and Former Pseudomonas: Detection of Recycling Enzymes Using High-Performance Liquid Chromatography

Abstract: Pyrimidine salvage pathways are vital for all bacteria in that they share in the synthesis of RNA with the biosynthetic pathway in pyrimidine prototrophs, while supplying all pyrimidine requirements in pyrimidine auxotrophs. Salvage enzymes that constitute the pyrimidine salvage pathways were studied in 13 members of Pseudomonas and former pseudomonads. Because it has been established that all Pseudomonas lack the enzyme uridine/cytidine kinase (Udk) and all contain uracil phosphoribosyl transferase (Upp), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Very recently it has been shown that P. aeruginosa mutants resistant to 5-FC spontaneously arise after long-term treatment with 5-FC in human serum, and whole genome sequencing revealed that these mutants invariably carried mutations in the upp gene (Rezzoagli et al, 2018), which encodes the uracil phosphoribosyltransferase responsible for conversion of uracil into the nucleotide precursor UMP in the pyrimidine salvage pathway (Beck and O'Donovan, 2008). To verify whether upp mutations were also present in our spontaneous 5-FU resistant mutants, we sequenced the entire upp gene, including its promoter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently it has been shown that P. aeruginosa mutants resistant to 5-FC spontaneously arise after long-term treatment with 5-FC in human serum, and whole genome sequencing revealed that these mutants invariably carried mutations in the upp gene (Rezzoagli et al, 2018), which encodes the uracil phosphoribosyltransferase responsible for conversion of uracil into the nucleotide precursor UMP in the pyrimidine salvage pathway (Beck and O'Donovan, 2008). To verify whether upp mutations were also present in our spontaneous 5-FU resistant mutants, we sequenced the entire upp gene, including its promoter.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate this aspect, in this work we analyzed two highly-related antivirulence drugs endowed with significant antivirulence activity and different impact on P. aeruginosa growth, namely the fluorinated pyrimidine analogs 5-FU and 5-FC (Figure 1, Supplementary Figure 1; Kirienko et al, 2016). The growth inhibitory activity of 5-FU allowed us to easily select spontaneous 5-FU-resistant mutants, which were characterized by loss-of-function mutations in the upp gene, responsible for conversion of uracil into the nucleotide precursor UMP in the pyrimidine salvage pathway (Figures 3, 4, Supplementary Table 1; Beck and O'Donovan, 2008). This implies that the growth inhibitory activity of 5-FU is mainly related to inhibition of nucleic acid synthesis, as it has been proposed to occur in yeasts and cancer cells (Vermes et al, 2000; Longley et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the overexpression of CTP synthase (citidine triphosphate synthase, pyr G gene, Q8CNI2) supports the de novo biosynthesis of the nucleotide cytosine by catalyzing the ATP-dependent amination of the UTP pyrimidine ring at 4-position to obtain CTP using either L-glutamine or ammonia as a nitrogen source (Endrizzi et al, 2004). Other proteins such as uridine kinase (udk gene, Q8CSB2) highlight the effort bacteria mount in pyrimidine biosynthesis by activating the salvage pathway, resulting in pyrimidine biosynthesis in a more cost-effective way (Beck and O’Donovan, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There were 4 different types of mutations, including two different nonsynonymous SNPs, a 15-bp deletion and a 1-bp insertion ( Supplementary Table S3 ). The upp gene encodes for a uracil phosphoribosyl-transferase, an enzyme required for the intra-cellular activation of flucytosine [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%